Understanding the resumability of tasks and behaviours when vision is disrupted while driving An occlusion and eye tracking evaluation - Guzman Sierra, Montserrat (2016)
Driver distraction is one of the main causes of road accidents. The increasing use of in-vehicle information systems (IVIS) by drivers whilst the vehicle is in motion, is expected to increase the number of road accidents caused by driving distraction. Distraction in this case is caused by deviating the attention from driving critical activities towards the completion of other activities on IVIS. The measurement of visual demand and resumability utilizing occlusion technique has not provided enough understanding on the visual behaviours required for the use of IVIS, creating a gap in understanding how IVIS could minimize driver distraction with the implementation of designs based on visual patterns, visual behaviours and visual demand. To investigate this gap, the study combined visual occlusion and eye tracking technique, providing insight to key visual behaviours performed for the completion of tasks when vision is interrupted and resumed, combining key occlusion metrics, visual demand, ease of resumability of tasks and error rate on task execution, to understand the visual behaviours associated with the completion of tasks. Ten participants carried out two tasks, under static and occlusion conditions, utilizing eye tracking glasses. Five main visual patterns were identified for the completion of tasks; different visual strategies were identified for the completion of each task. It is concluded that occlusion and eye tracking provide useful information for the design of IVIS, and that the performance of tasks are highly impacted by the resumption of these.